Port Service Industries : the case of Montreal - Slack, Brian (Cahiers de géographie du Québec, 1982)
Ports generate significant benefits to local economies. Most major port cities have an important tertiary sector of port service industries. The nature, scale and geographical location of this industry is poorly understood however. This study describes the character and evolution of Montreal's port service industry. It analyses the locational determinants of a wide range of activities that are marine related, and discusses the patterns that are evolving as a result of developments in shipping technology and changing urban patterns.